Dissemination, sharing and appropriation of information on YouTube: an analysis of the LGBTQ channel Ptie na Roda - Martinez-Avila, Daniel; Luvizotto, Caroline Kraus [UNESP]; Brito, Jean Fernandes [UNESP]; Silva, Rafaela Carolina da [UNESP] (Univ Federal Santa Catarina, 2020)
Objective: When working with the social and historic context of Lesbian, Gay, Bisexual, Transgender and Queer (LGBTQ) people, it is possible to see the existence of several dimensions of visibility in physical and virtual spaces where a community is created to strengthen the movement. In this sense, this paper studied the ways in which the POe na Roda YouTube channel works with the dissemination of information for the appropriation of LGBTQ information. Methods: The research method was a netnography, with qualitative and exploratory approaches to an applied study in order to analyze the video Opcao Sexual: voce nasceu ou virou hetero?, based on the criteria of 'more views' and 'more comments.' Results: The exchange of information can be perceived both in the youtuber and in the ways of the relationships between the audience and platform, giving the users knowledge on how to face information needs on the topic of the channel. This aspect reveals the youtuber's concern and commitment as a professional who disseminates information and at the same time makes videos in a coherent way in order to mediate the information to the users. Conclusions: The LGBTQ's movement appropriates and shares information between its community in the YouTube platform and the youtubers. Thus, we observed the importance of platforms such as YouTube for the Information Science field as these environments complement the information processing and the generation of knowledge in society.
Keywords: Dissemination of information; Appropriation of information; LGBTQ community POe na Roda channel